Positive Effects of Physical Activity on Prescription on Glycemic Control, Fitness, and Quality of Life in Newly Diagnosed Type 2 Diabetic Patients - Nguyen, Tam Ngoc; Vu, Huyen Thi Thanh; Khuong, Long Quynh; van der Ploeg, Ingeborg; Sundberg, Carl Johan (Hormone and Metabolic Research, 2023)
The aim was to investigate the effects of physical activity on prescription (PAP) compared with standard care (SC) in adult drug-naïve T2D patients. A randomized control trial was conducted with drug-naïve T2D patients attending an out-patient clinic Vietnam. Participants were randomly assigned to the PAP group (n+=+44) or the SC group (n+=+43). The PAP group received individualized recommendations for PA, intensive face-to-face training every two weeks. The SC group received the standard recommendations according to WHO guidelines. The mean HbA1c level change was larger (–10.6±6.4 mmol/mol) in the PAP group than in the SC group (–2.4±5.8 mmol/mol) (p<0.001). A one thousand step counts per day increase was significantly associated with a decrease of –2.43 mmol/mol in HbA1c [β=–2.43, 95%CI: (–2.94, –1.92]) in the PAP group. The fasting plasma glucose levels of the PAP group decreased significantly compared with the SC group. The VO2-max increased significantly more in the PAP group than in the SC group. PAP had clear positive effects on health-related Quality of Life [mean between group difference: 9.54 (95%CI 5.84,13.23)]. Insulin resistance, BMI, waist circumference, total cholesterol, LDL cholesterol and triglycerides were significantly more decreased in the PAP group than in the control group. In conclusion, the fact that even a small change in mean step counts over three months had a beneficial effect on health-related outcomes in drug-naïve T2D patients can have large implications for treatment and management practices, not least in a middle-income country like Vietnam.
Keywords: exercise; Vietnam; diabetes